Altering crop management practices to promote pollinators - Franco, Jose G. (Burleigh Dodds Series in Agricultural Science, 2023)
Agricultural intensification, or the increase in crop production per unit of input or land area to meet the needs of a growing population, has resulted in a landscape dominated by large scale monoculture cropping. Pollinators, specifically, are impacted by the lack of diverse floral and habitat resources associated with this type of farming. Agriculture must develop practices that diversify the crop landscape and increase the availability of habitat and flowering resources to support these populations. In this chapter, we summarize the available literature on how the production space, i.e., within a crop production field, orchard, or pasture, can be more effectively managed to sustain pollinator populations. We report on various spatial and temporal approaches within the context of various cropping systems (row crops, specialty crops, perennial orchards, and perennial forage and pasture systems). Collectively, these approaches represent opportunities to re-introduce diversity into the agricultural landscape to benefit pollinators.